1998
DOI: 10.2307/2640955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Invasive, Non-Indigenous Plant Species on Ecosystem Processes: Lessons from Florida

Abstract: Individual plant species that modify ecosystem properties have traditionally been thought to be uncommon in natural systems. I hypothesize that many invasive nonindigenous species do alter these properties at several scales. The non-indigenous plant species in Florida considered the most invasive by the Florida Exotic Pest Plant Council are examined for this capability through review of the available literature. Out of 31 species total, 12-20 (39-64%) potentially alter the ecosystem properties of geomorphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(202 citation statements)
references
References 35 publications
4
196
0
2
Order By: Relevance
“…Similarly, a decline in the N supplied to microbial communities occurs in response to the invader Bromus tectorum (Evans et al, 2001). Other studies have also suggested that invasive plants may modify ecosystem properties, modulating the availability of resources to other species (DÕAntonio and Vitousek, 1992;Gordon, 1998;Mack et al, 2000;Vitousek et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a decline in the N supplied to microbial communities occurs in response to the invader Bromus tectorum (Evans et al, 2001). Other studies have also suggested that invasive plants may modify ecosystem properties, modulating the availability of resources to other species (DÕAntonio and Vitousek, 1992;Gordon, 1998;Mack et al, 2000;Vitousek et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the frequency and impact of non-natives will increase significantly over the next several decades (Ellison et al, 2005;Lodge et al, 2006). Non-native species have the 150 J. M. VOSE et al potential to significantly alter ecohydrological function (Gordon, 1998) and reduce the capacity of forested watersheds to provide clean and abundant water, as well as support diverse, healthy aquatic ecosystems, and native faunas. Although some information exists on the direct impacts of aquatic non-native species on aquatic ecosystem structure and function, we know considerably less about the impacts of non-native species on water quantity and quality (Hooper et al, 2005).…”
Section: Invasive Speciesmentioning
confidence: 99%
“…Sin embargo, indistintamente de la causa que lleva a que una planta se convierta en invasora, pueden llegar a alterar las interacciones entre especies y las condiciones ambientales (Vitousek et al, 1987;D'Antonio y Vitousek, 1992;Gordon, 1998), dando como resultado cambios en la composición de las comunidades y pérdidas en la biodiversidad.…”
Section: Yazmín Escutia-lara Y Roberto Lindig-cisnerosunclassified